Molecular mechanisms of SNAC1 (Stress-responsive NAC1) in conferring the abiotic stress tolerance - Kurowska, Marzena (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023. Published by Elsevier B.V.